Atención integral del neonato con encefalopatía hipóxico-isquémica en España - Juan Arnaez; Nuria Herranz-Rubia; Alfredo Garcia-Alix; J. Diez-Delgado; I. Benavente-Fernández; I. Tofé; A.E. Jerez; J.A. Hurtado; J.M. Ceballos; M.L. Millán; M.D. Esquivel; C. Ruiz; et al. (Elsevier, 2020)
Resumen: Introducción: Apenas conocemos cómo es la asistencia de los recién nacidos (RN) con encefalopatía hipóxico-isquémica (EHI) en hipotermia terapéutica (HT), especialmente si existen protocolos asistenciales, la neuromonitorización que se realiza o cómo es la aproximación al pronóstico neurológico. Este conocimiento permite detectar e implementar áreas de mejora asistencial. Método: Estudio transversal de los 57 hospitales españoles que realizaban HT en 2015, mediante cuestionario sobre: 1) la disponibilidad de protocolos y de recursos tecnológicos; 2) el uso de herramientas de neuromonitorización; 3) los conocimientos de los profesionales; 4) la información pronóstica que se da los padres, y 5) el informe al alta y del plan de seguimiento. Resultados: El 95% utiliza enfriamiento corporal-total servocontrolado y dispone de protocolos específicos de actuación. El 70% utiliza sedación y el 68% deja al paciente a dieta absoluta. La monitorización con electroencefalografía integrada por amplitud se utiliza en más del 80% de los centros, aunque solo en el 50% la enfermera es capaz de interpretarlo. La saturación de oxígeno cerebral es escasamente monitorizada (16%). Entre los estudios diagnóstico-pronósticos, la neuroimagen es universal, pero los neurobiomarcadores apenas se utilizan (29%). Solo el 21% ofrece información pronóstica antes de las 72 h de vida; sin presencia de la enfermera en el 70%. El seguimiento lo realiza el neuropediatra (84%), con una duración desigual entre centros. Conclusiones: La asistencia del RN con EHI en España es adecuada, con áreas de mejora en: neuromonitorización, sedación, marco temporal de la información pronóstica, trabajo en equipo y estandarización de la duración del seguimiento. Abstract: Introduction: There is not much information about the care of infants with hypoxic-ischaemic encephalopathy (HIE) treated with therapeutic hypothermia (TH) in Spain. This includes whether protocols are routinely used, the type of neuro-monitoring performed, and how information on the neurological prognosis is presented to families. The answers to these would allow to detect and implement areas of improvement. Method: A cross-sectional analysis was performed on the responses to structured questionnaires sent to all the Spanish neonatal units that were performing TH in June 2015. Questions were divided into 5 sections: 1) the availability of protocols and technological resources, 2) the use of neuro-monitoring tools, 3) the knowledge and training of the professionals; 4) the prognostic information given to the parents; and 5) the discharge report and the follow-up plan. Results: Most centres (95%) use servo controlled whole-body cooling methods and have specific management protocols. Sedation is used in 70% of centres, and in 68% of them the onset of enteral feeding is delayed until the end of the cooling period. Amplitude-integrated electroencephalography monitoring is used in more than 80% of the centres, although only in 50% are nurses able to interpret it. Cerebral oxygen saturation is not often monitored (16%). As regards diagnostic-prognostic studies, neuroimaging is universal, but brain damage biomarkers are hardly used (29%). Prognostic information is offered within the first 72 posnatal hours in 21% of the centres, and is given without the presence of the nurse in 70% of the centres. Follow-up is performed by a neuro-paediatrician (84%), with an uneven duration between centres. Conclusions: The care of infants with HIE treated with TH in Spain is generally adequate, although there are areas for improvement in neuromonitoring, sedation, prognostic information, teamwork, and duration of follow-up.